2018
DOI: 10.1007/s10858-018-0187-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid measurement of long-range distances in proteins by multidimensional 13C–19F REDOR NMR under fast magic-angle spinning

Abstract: The ability to simultaneously measure many long-range distances is critical to efficient and accurate determination of protein structures by solid-state NMR (SSNMR). So far, the most common distance constraints for proteins are C-N distances, which are usually measured using the rotational-echo double-resonance (REDOR) technique. However, these measurements are restricted to distances of up to ~ 5 Å due to the low gyromagnetic ratios of N andC. Here we present a robust 2D C-F REDOR experiment to measure multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 35 publications
(52 reference statements)
4
70
1
Order By: Relevance
“…Mixing of fluorinated protein with 13 C-labeled protein does not affect the protein conformation, as verified by identical 13 C chemical shifts (data not shown). Two 13 C spectra were measured without (S 0 ) and with (S) 19 F pulses using the rotational-echo double-resonance (REDOR) experiment 35 , 36 . To ensure that the distance-dependent dipolar couplings are not averaged by motion, we measured the REDOR spectra in the gel-phase membrane where the protein is immobilized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixing of fluorinated protein with 13 C-labeled protein does not affect the protein conformation, as verified by identical 13 C chemical shifts (data not shown). Two 13 C spectra were measured without (S 0 ) and with (S) 19 F pulses using the rotational-echo double-resonance (REDOR) experiment 35 , 36 . To ensure that the distance-dependent dipolar couplings are not averaged by motion, we measured the REDOR spectra in the gel-phase membrane where the protein is immobilized.…”
Section: Resultsmentioning
confidence: 99%
“…Powder averaging used the REPULSION320 scheme 59 with 64 γ angles. The REDOR simulations accounted for finite 19 F and 13 C 180° pulse lengths, 19 F pulse imperfections, and 19 F chemical shift anisotropy (CSA) 36 . The 19 F pulse imperfection was treated by adding REDOR curves for 19 F pulse flip angles of 180° to 145° using weights that match a normal distribution centered at 180° with a standard deviation of 15° 36 .…”
Section: Methodsmentioning
confidence: 99%
“…Only three recent studies used faster spinning frequencies. In two, resolution enhancements were observed at 35 and 40 kHz, [14, 26] while a report from our group demonstrated that frequencies of 40–60 kHz yielded significant line narrowing for fluorosubstituted tryptophan solids, thus alleviating the need for 1 H decoupling. [27] …”
mentioning
confidence: 99%
“…To further test the hemifusion structural model, it will be important to obtain additional long-range distance restraints. These may be obtained from paramagnetically tagged protein or fluorinated protein by exploiting paramagnetic relaxation enhancement or 19 F distance NMR techniques (32)(33)(34)(35), respectively. Finally, mixed labeled protein samples will be important to determine the oligomeric structure of this gp41 hemifusion intermediate.…”
Section: Hiv Gp41 Conformation From Ssnmrmentioning
confidence: 99%